Anesthetic Complication during Maxillofacial Trauma Surgery: A Case Report of Intraoperative Tension Pneumothorax. Issue 3 (September 2016) - Al Shetawi, AlHaitham; Golden, Leonard; Turner, Michael
Tension pneumothorax is a life-threatening emergency that requires a high index of suspension and immediate intervention to prevent circulatory collapse and death. Only five cases of pneumothorax were described in the Oral and Maxillofacial Surgery literature. All cases were postoperative complications associated with orthognathic surgery. We report a case of intraoperative tension pneumothorax during a routine facial trauma surgery requiring emergency chest decompression. The possible causes, classification, and reported cases will be presented.